Caste, Space, and Retail Religiosity in Tamil Toronto - Mark P. Whitaker (Caste)
This paper is focused on ritually organized caste practices in the Canadian Sri Lankan Tamil diaspora. It describes how Sri Lankan Tamils in Toronto, Canada, who in some ways have tried to turn their backs on caste (especially in the second and third generations), nonetheless use caste as a sort of marketing “brand” in an increasingly competitive Hindu temple “market”. This paper is animated by an underlying concern with how spatial aspects of Sri Lankan Tamil religious life were formed and transformed in diaspora in ways that altered also what it means to act and be a Tamil person. It is important to note, however, that what is at issue here is not simply the effect on diaspora Tamil forms of exclusionary sociality (in this case, caste) due to the loss of an imagined or real territory – a traditional concern of diaspora studies and its worries about nostalgia – but rather changes in the religiously mediated relationship, via caste, between Tamil people and their landscapes, and hence changes forced upon social relations by confrontations with shifting or entirely new political geographies of an anxious world.